Hybrid (Virtual and In-Person) Training on DTREO: A Digital Genetic Database - Getachew, Tesfaye; Rekik, Mourad; Rischkowsky, Barbara A.; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Virtual and face-to-face trainings on DTREO, a digital genetic database, was organized in 2023 for research and development partners in Tunisia. A total of 11 participants, including five women from the National Research and Development Office of Tunisia, attended the training. The sessions highlighted the importance of a digital database for genetic evaluations and introduced the features of DTREO, such as offline data capture and quick feedback. The training covered data entry options, data configuration, and reporting capabilities and included a practical session on preparing the master file and loading data. Overall, the training aimed to equip participants with the knowledge and skills to use DTREO effectively in their small ruminant breeding programs. Following the training, significant progress has been achieved as 337 historic sheep pedigrees and performance data from three villages (Rahala, Sers, and Elles) have been successfully loaded into the DTREO system.